Waist-holding type extraction machine in disc casting machine - WU QIANG; HE ZEGAN; LIU YANSHUN; XUAN PEIJIAN (2012)
The utility model relates to an improvement of an extraction device of a disc casting machine, namely, the way of an extraction anode plate of the disc casting machine is changed from the lug grabbing type to the waist holding type. At present, the extraction ways of the most of the disc casting machines adopt the lug grabbing type, the disc casting machines are easy to fall from high places, and the anode plates (very thin) are subject to deformation, so that the qualified anode plates can not be produced and safety accidents are easy to occur. The improved extraction device disclosed by the utility model comprises a main shaft, wherein an extraction arm and a shaft encoder are mounted at one end of the main shaft, and an extraction mechanism is fixed at the upper end of the extraction arm; and the extraction mechanism comprises a driven shaft which is fixed with the upper end of the extraction arm and a mounting plate which is fixed with the driven shaft together, as well as a fixed frame, the fixed frame a